The Socioeconomic Status of Polish Pensioners Before and After Migration - Pytel, Sławomir Piotr; Kiniorska, Iwona (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The aim of this paper is to describe the socioeconomic status of migrating seniors before and after migration. This analysis will enable us to determine whether the overall effect of their migrations is a positive one or a negative one. In order to determine subjective reasons for migrations, questionnaire surveys are used. An analysis of the responses allows us to compare the migrants’ living conditions before and after migration with a view to confirming or rejecting Wolpert’s (1965) assumptions and to describe the role of migrations in meeting pensioners’ needs. Our study confirms the approach of Wolpert (1965), assuming that the behaviour of migrants, including migrating pensioners, is determined by place utility, i.e. the sum of advantages to be obtained by the migrant. The pensioners who migrated are well‑off, our respondents report that they are able to meet all their needs if spending money prudently.